Phenotypic plasticity in Drosophila cactophilic species: the effect of competition, density, and breeding sites - Fanara, Juan Jose (2017)
Changes in the environmental conditions experienced by naturally occurring populations are frequently accompanied by changes in adaptive traits allowing the organism to cope with environmental unpredictability. Phenotypic plasticity is a major aspect of adaptation and it has been involved in population dynamics of interacting species. In this study, phenotypic plasticity (i.e., environmental sensitivity) of morphological adaptive traits were analyzed in the cactophilic species Drosophila buzzatii and Drosophila koepferae (Diptera: Drosophilidae) considering the effect of crowding conditions (low and high density), type of competition (intraspecific and interspecific competition) and cacti hosts (Opuntia and Columnar cacti). All traits (wing length, wing width, thorax length, wing loading and wing aspect) showed significant variation for each environmental factor considered in both Drosophila species. The phenotypic plasticity pattern observed for each trait was different within and between these cactophilic Drosophila species depending on the environmental factor analyzed suggesting that body size-related traits respond almost independently to environmental heterogeneity. The effects of ecological factors analyzed in this study are discussed in order to elucidate the causal factors investigated (type of competition, crowding conditions and alternative host) affecting the election of the breeding site and/or the range of distribution of these cactophilic species.